2013
DOI: 10.1182/blood-2012-08-449413
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocytes represent a novel MDSC subset circulating in patients with metastatic cancer

Abstract: Key Points Myeloid cells in subjects with cancer contain fibrocytes, a cell subset previously implicated in chronic inflammation. Fibrocytes in cancer patients are immunosuppressive and may contribute to immune escape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 54 publications
5
139
2
Order By: Relevance
“…Many studies have reported that COX-2 expression is usually upregulated in human cancers, including NPC. 34,44,45 COX-2 activity is detected throughout the progression of a premalignant lesion to a metastatic phenotype. Increased expression of COX-2 is associated with angiogenesis, decreased host immunity, enhanced invasion and metastasis in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that COX-2 expression is usually upregulated in human cancers, including NPC. 34,44,45 COX-2 activity is detected throughout the progression of a premalignant lesion to a metastatic phenotype. Increased expression of COX-2 is associated with angiogenesis, decreased host immunity, enhanced invasion and metastasis in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…on their surfaces Gunaydin et al 2015). According to Zhang et al (2013), F-MDSCs might express HLA-DR unlike other human MDSCs. Although it is clear that F-MDSCs with fibrocytic phenotypes show immunosuppressive functions, little is known how F-MDSCs differentiate from common HSCs and suppress T cells.…”
Section: The Subsets Of Mdscsmentioning
confidence: 99%
“…Recently, fibrocytic MDSCs (F-MDSCs) are characterized as a novel MDSC subset in human (Abrams and Waight 2012;Zhang et al 2013;Mazza et al 2014;Zoso et al 2014;Gunaydin et al 2015). F-MDSCs show tumorassociated circulating fibrocyte phenotypes and have T cell-mediated immunosuppressive functions.…”
Section: The Subsets Of Mdscsmentioning
confidence: 99%
See 2 more Smart Citations